Validity of modified early warning, Glasgow Blatchford, and pre-endoscopic Rockall scores in predicting prognosis of patients presenting to emergency department with upper gastrointestinal bleeding. Issue 1 (December 2015) - Bozkurt, Seyran; Köse, Ataman; Arslan, Engin; Erdoğan, Semra; Üçbilek, Enver; Çevik, İbrahim; Ayrık, Cüneyt; Sezgin, Orhan
Abstract Background GBS, MEWS, and PER scoring systems are not commonly used for patients presenting to emergency department with GIS bleeding. This study aimed to determine the value of MEWS, GBS, and PER scores in predicting bleeding at follow-up, endoscopic therapy and blood transfusion need, mortality, and rebleeding within a 1-month period. Methods A total of 202 consecutive patients with upper GIS bleeding between July 2013 and November 2014 were prospectively enrolled in the study. The relationship between MEWS, GBS, and PER scores and hospital outcome, bleeding at follow-up, endoscopic therapy, transfusion need, rebleeding, and death were examined. Results The study included a total of 202 subjects, with 84 (41.6 %) females and 118 (58.4 %) males. There was a significant correlation between GBS, MEWS, and PER scores and hospital outcomes (p  <0.004, p  <0.001, p <0.001, respectively). A GBS score greater than 11 succesfully predicted bleeding at follow-up (p  = 0.0237). GBS score's sensitivity for predicting endoscopic therapy was greater than those of other scoring systems. The discriminatory power of each scoring system was significant for predicting transfusion (p  <0.0001, p  = 0.0470, andp  = 0.0014, respectively). A GBS score greater than 13, a MEWS score greater than 2, and a PER score greater than 3 predicted death. A PER score greater than 3 predicted rebleeding (p  <0.0001). Conclusion The scoring systems in question can be easily calculated in patients presenting to ED with upper GIS bleeding and may be beneficial for risk stratification, determination of transfusion need, prediction of rebleeding, and decisions of hospitalization or discharge.